دراسة واقع مؤشرات التنمية الصحية في الجمهورية العربية السورية ما بين عامي 2000-2010 - محمود, حبيب; أسعد, باسل أنور (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت الدراسة إلى تحليل واقع مؤشرات التنمية الصحية في الجمهورية العربية السورية مابين عامي 2000-2010 بغية معرفة مدى التطور الحاصل في قطاع الخدمات الصحية خلال فترة الدراسة. كما ركزت الدراسة على ثلاث مؤشرات أساسية وهي: مؤشرات صحية اقتصادية، مؤشرات صحية خدمية، مؤشرات صحية تتعلق بانتشار المرض خلال فترة الدراسة. قام الباحث بدراسة وتحليل المؤشرات الصحية الأساسية الثلاث وإظهار إيجابياتها وسلبياتها ضمن سورية ومقارنتها مع بعض الدول العربية المحيطة ومدى تأثرها وانعكاسها على عملية التنمية في سورية. كما توصلت الدراسة إلى مجموعة من النتائج أهمها: إن انخفاض الإنفاق الحكومي على قطاع الصحة قد آثر بشكل سلبي على العديد من مؤشرات التنمية الصحية في سورية. عدم تناسب توزيع الخدمات الصحية حسب المحافظات وعدم عدالتها. تحسن العديد من مؤشرات التنمية الصحية المتعلقة بالأمراض السارية والوفيات على الرغم من احتلال سورية موقع متوسط مقارنة مع بعض الدول العربية.This study has aimed to analyze the fact of the health development indictors in Syrian Arab Republic between 2000-2010. And the analysis has been done in order to know the development level of health service sector during the study period. This study focuses on three main indicators, which are: Economic healthy indicator. Service healthy indicator. Healthy indicator related to disease spread during the period of this study. The researcher has studied and analyzed the three main healthy indicators and has shown their advantages and disadvantages in Syria. Moreover, he has made a comparison between them and those in some neighbor Arab countries, and showed how sensitive to and affective they are in the development process in Syria. The study has achieved a set of results; the most important are: the decline of the government expenditure on the Health Sector affected in many healthy development indicators. The disproportion and injustice of distribution of the healthy services to cities. The improvement of many healthy development indicators related to infectious diseases and death despite Syria's middle classification comparing with some Arab countries.